Discordance for placental mesenchymal dysplasia in a monochorionic diamniotic twin pregnancy: A case report. Issue 8 (22nd June 2018) - Gheysen, Willem; Strybol, David; Moerman, Philippe; Steylemans, An; Corveleyn, Anniek; De Catte, Luc; Couck, Isabel; Lewi, Liesbeth
Key Clinical Message: Placental mesenchymal dysplasia (PMD) occurs in about 1 in 5000 pregnancies. The differential diagnosis between PMD and partial mole is difficult on ultrasound scan, and karyotyping plays a key role in distinguishing PMD from partial mole. Our report is the first to report on the discordancy for PMD in a monochorionic setting. Abstract : Placental mesenchymal dysplasia (PMD) occurs in about 1 in 5000 pregnancies. The differential diagnosis between PMD and partial mole is difficult on ultrasound scan, and karyotyping plays a key role in distinguishing PMD from partial mole. Our report is the first to report on the discordancy for PMD in a monochorionic setting.